Changes of Neuroretinal Rim and Retinal Nerve Fiber Layer Thickness Assessed by Optical Coherence Tomography After Filtration Surgery in Glaucomatous Eyes - Koenig SF (Dove Medical Press, 2021)
Susanna Friederike Koenig,1 Christoph Wolfgang Hirneiss2 1Moorfields Eye Hospital NHS Foundation Trust, London, EC1V 2PD, UK; 2Ludwig-Maximilians University, Eye Clinic, Campus Innenstadt, Munich, D-80336, GermanyCorrespondence: Susanna Friederike KoenigMoorfields Eye Hospital NHS Foundation Trust, 162 City Road, London, EC1V 2PD Email susanna.koenig@nhs.netPurpose: Lowering the intraocular pressure (IOP) in patients with primary open-angle glaucoma (POAG) with filtration surgery can induce morphological changes to the bulbus and structures of the retina. In this study, we have evaluated changes of Bruch’s membrane-based parameters and retinal nerve fiber layer (RNFL) derived by spectral-domain optical coherence tomography (SD-OCT) in eyes that have undergone glaucoma filtration surgery.Patients and Methods: SD-OCT imaging of the optic nerve head (ONH) and of the RNFL was performed in 54 eyes of 54 patients with medically uncontrolled POAG before and after IOP-lowering surgery (trabeculectomy or deep sclerectomy). The ONH parameter minimum rim width (MRW) and the size of the Bruch’s membrane opening (BMO-Area) were derived from 24 radial B-scans centered on the ONH.Results: The average preoperative IOP was 23.1 ± 7.5 mmHg. One month postoperatively, the average IOP decreased to 12.1 ± 4.6 mmHg (p < 0.01), which caused a significant increase in the thickness of neuroretinal rim. There was no significant change in the automatically detected BMO-Area (p = 0.32). The pressure-related increase in MRW correlated well with the postoperative IOP and cup-to-disc ratio (CDR). In regression analysis, the alteration in thickness of the neuroretinal rim could be well predicted in a model including CDR, change of IOP and mean deviation (MD) (R2 = 0.414, p < 0.001). RNFL showed a significant increase as well.Conclusion: IOP-lowering surgery in patients with medically uncontrolled POAG causes an increased thickness of the SD-OCT derived ONH parameters. The changes of the RNFL after surgery showed no significant correlations with IOP changes. In contrast to this, highly significant correlations of MRW values with the IOP could be observed. The BMO-Area remained completely stable A preferred use of RNFL for follow-up should be discussed.Keywords: glaucoma, optic nerve head, ONH, OCT, retinal nerve fiber layer, RNFL, Bruch’s membrane opening, BMO